Anna Banana and me - Blegvad, Lenore; Blegvad, Erik (New York : Aladdin Paperbacks, 1987)
Anna Banana's fearlessness inspires a playmate to face his own fears.
"Aladdin picture books"--Cover.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
2.4
K-3
Keywords: Fear -- Fiction; Fear -- Fiction